Um estudo sobre equações: identificando conhecimentos de alunos de um curso de formação de professores de Matemática - Pereira, Marcelo Dias (2005)
This paper is part of the G5 Group of Studies on Algebra Education, included in the Program of Graduate Studies in Mathematics, from the Pontifícia Universidade Católica in Sao Paulo, and more specifically, in the What kind of Algebra should be taught in Courses for Mathematics Teachers? Project. It is a qualitative Case Study based on investigative testing through bibliographic and documentary research. The study s main objective is to identify the level of knowledge of Equations among students who enrolled in the Mathematics Undergraduate Degree Program in a private Education Institution in the State of Sao Paulo in 2005. Among other results, obtained from the analysis of codification categories, according to Bogdan & Biklen (1994), the conclusion is that the majority of the students regard an Equation as a procedure for determining an unknown value, without, however, using it as a problem solving tool. This group of students is undergoing the critical stage of building competencies and developing skills, according to the 2003 SAEB (Brazilian Elementary Education Evaluation System), which ratifies the 2003 SAEB s data on Mathematics Education and the 1997 SARESP (Student Output Evaluation System in the State of Sao Paulo) results, thus indicating the existence of a gap in this small area of Algebra in Elementary Education, addressed by the What kind of Algebra should be taught in Courses for Mathematics Teachers? Project.